Association between Cystatin C and cardiac function in acute myocardial infarction patients: a real-world analysis - Lou, Bowen; Luo, Yongbai; Zhang, Haoxuan; Wu, Haoyu; Jiang, Gulinigaer Tuerhong; Liu, Hui; Kan, Kejia; Hao, Xiang; Sun, Lizhe; Yuan, Zuyi; She, Jianqing (Disease markers, 2022)
Background. Acute myocardial infarction (AMI), as well as its long-term and short-term complications, is known to present with high morbidity and mortality. Cardiac function deterioration and ventricular remodelling after AMI are known to be correlated to worse long-term outcomes. However, the underlying mechanism remains elusive and there is a shortage of serum prediction markers. This study investigates the relationship between in-hospital Cystatin C (CysC) and cardiac function and subsequent prognosis among AMI patients. Research Design and Methods. We measured admission CysC and cardiac function parameters, including ejection fraction (EF) and pro-BNP value in 5956 patients diagnosed with AMI. Simple and multiregression analyses were performed to investigate the correlation between CysC and cardiac function in AMI patients. Major adverse cardiovascular events (MACE), cardiovascular, and all-cause mortality were documented, and 351 participants with high cystatin (≥1.09 mg/L) and 714 low cystatin (<1.09 mg/L) were investigated for survival analysis during a 48-month follow-up. Results. 5956 patients with AMI were enrolled in the initial observational analysis, and 1065 patients of the whole cohort were included in the follow-up survival analysis. The admission CysC level was found to be significantly positively correlated to the pro-BNP level (, 95% CI 4758 to 5265, ) and negatively correlated to the EF value (, 95% CI -3.503 to -1.605, ). Kaplan-Meier survival analysis revealed significantly increased MACE incidence (, 95% CI 1.400 to 3.755, ), cardiovascular mortality (, 95% CI 1.694 to 5.371, ), and all-cause mortality (, 95% CI 2.010 to 5.835, ) in high-admission CysC cohort with AMI at the end of 4-year follow-up. Conclusions. Admission CysC is negatively correlated with cardiac function in AMI patients and acts as a novel predictor for MACE incidence in the whole population. Further studies are needed to investigate the specific mechanism of CysC in the cardiac function deterioration among AMI patients.